The Economics of aging - Wise, David A. (Project report (National Bureau of Economic Research), 1989)
The Economics of Aging presents results from an ongoing National Bureau of Economic Research project. Contributors consider the housing mobility and living arrangements of the elderly, their labor force participation and retirement, the economics of their health care, and their financial status. The goal of the research is to further our understanding both of the factors that determine the well-being of the elderly and of the consequences that follow from an increasingly older population with longer individual life spans. Each paper is accompanied by critical commentary.